MANAJEMEN SEKOLAH IDEAL MELALUI PENDEKATAN SASTRA - SALAM, EVELINA SATRIYA (DIDAKTIKA, 2017)
Educational is a process o transferring o knowledge (science, technology and art) by teachers/lecturers to students. Moreover, education is atool to change the way of thinking from the traditional way to the scientific way. One important component in educational activities is the principal and teachers. The emergence of various books in the science o education management as a learning effort or principal and teacher do not make them aware of the contents of the book. In general, the science of education management books is more theoretical. “Sekolah Cinta” by Edi Sutarto tried to approach readers in the unique way. Its uniqueness lies on the content of the book which is not just a book of management education science but it is present as literature valuable work. This book provides a solution to the problem of the face of education in Indonesia by applying the approach see-do-get. In addition, the mindset change movement concept known as unfreezing-moving-freezing organizational cycle.